أثر المساءلة من منظور إسلامي في أداء المعلمين بالمدارس الحكومية في سلطنة عمان بولاية بوشر من وجهة نظر مديري المدارس ومساعديهم: THE IMPACT OF ACCOUNTABILITY FROM AN ISLAMIC PERSPECTIVE ON THE PERFORMANCE OF TEACHERS IN GOVERNMENT SCHOOLS IN THE SULTANATE OF OMAN, IN THE STATE OF BAUSHER, FROM THE POINT OF VIEW OF SCHOOL PRINCIPALS AND THEIR ASSISTANTS - Abdullah Al-Abri, Abdulsalam Salim; Mohamed Adnan , Mohamad Azrien; Jamil, Asyraf Isyraqi (Online Journal of Islamic Management and Finance (OJIMF), 2024)
This study aims to reveal the impact of accountability from an Islamic perspective on the performance of teachers in government schools in the Sultanate of Oman in the state of Bausher. And in their relations during the practice of the educational process, and the importance of the study lies in an attempt to shed light on the importance of knowing the impact of accountability from an Islamic perspective on the performance of teachers, and the researchers used a random sample consisting of (24) school principals and assistant principals in government schools in the state of Bausher, and they were chosen using the intentional sampling method, In the way it was prepared, this study relied on the analytical descriptive approach, and the researchers used the questionnaire as a tool for data collection, which consisted of the field of accountability from an Islamic perspective, and the field of teacher performance. The independent variable (accountability) included four dimensions: (discipline, achievement, professional ethics, human relations ), and to extract the results from the questionnaire, the extracted data were processed by using statistical packages for social sciences (SPSS), and the results of the study showed that there is a positive effect of accountability from an Islamic perspective in the performance of teachers from the point of view of school principals and their assistants according to its four dimensions, and the study recommended to instill the principle of accountability subjectivity based on the Islamic perspective, with the importance of linking the outcomes of accountability with reward and according to the Islamic perspective.